Creating innovation through collaboration - partnering in the maritime sector - Henriette Sophia Groskopff Tvede Schleimann (Copenhagen Business School (CBS), 2019)
Innovation and optimization are essential elements for organizations worldwide, as these will ensure the survival ahead for the organizations. The competition in the markets are different from that 10 years ago, and will probably have changed again 10 years from now, because of the technological development. This means that - to a greater extent - it is important to be first mover in the attempt to create new and improved products. Additionally, it is important to optimize the organization's processes by focusing on its primary business purpose and outsource those elements which are not value creating. In the organization's striving toward optimized products and processes, strategic alliances are getting increasingly important between industries and between various global organizations.
hdl:10398/9747
Keywords: 650; Wettbewerb; Unternehmenskooperation; Innovation; Reederei; Vertrag